Pelatihan Sharaf Bab Al-Mazid As Sudasy Bagi Santri Binaan Cmm Ponpes Al-Firqatun Najiyah Malang - Achmad Tito Rurady; Suherman suherman (Institut Agama Islam Sumatera Barat, 2025)
Sharaf is a very important part of Arabic language learning, which is also an inseparable part of the world of Islamic boarding schools. This training aims to help students master tashrif ishtilahiy in the chapter of mazid as sudasy. This training activity was held at al-Firqotun Najiyah Islamic boarding school in Malang district. The method used in this activity in general is an eclectic method, which is a combination of several methods needed according to the needs and conditions in the field. The specific methods that the proposer offers are the talqin and takrar methods. The talqin method is a way of dictating to the audience properly and correctly. The takrar method is the repetition/repetition of words. The results of the service showed that it was well organized even though there were still some obstacles such as too many participants, and relatively short time. All the material in this mentoring has been delivered entirely to the mentoring participants. Of the 40 participants, 87.5% have understood the chapter of al mazid as sudasy and 12.5 %, have not understood it, this is due to the large number of participants while the material is delivered in a short time